Organoleptic Characteristics of Functional Biscuit enriched with Protein and Betacaroten - Dewi Kartika Sari; Agustiana Agustiana; Findya Puspitasari (TROPICAL WETLAND JOURNAL, 2019)
One of the fishery products that have great potential for solutions in the effort to handling nutrition cases is snakehead fish as a source of protein and pumpkin as a source of beta-carotene. This study aimed to determine the effect of variations in biscuit formula by supplementation snakehead fish meal and pumpkin flour to the characteristics of organoleptic functional biscuits and obtaining functional biscuit formulas with organoleptic characteristics can be received by the panelist. The main ingredients of this study are snakehead fish meal and pumpkin flour. Fish meal maker tools include oven and flour blender, as well as biscuit making tools, include baking pan, mold, mixer, and oven. The results of this study indicate that variations in biscuit formulas with supplementation of cork and pumpkin fish meal significantly affected the characteristics of organoleptic functional biscuits. Functional biscuit formula with a ratio of 75% wheat flour, 12.5% snakehead fish meal, 12.5% pumpkin flour (comparison of 3 parts wheat flour with 2 parts mixture of fish flour and pumpkin/ 3: 1) selected as the best formula. The conclusion showed that functional biscuits rich in protein and beta-carotene with supplementation of snakehead fish meal and pumpkin flour (ratio 3: 1) can be an option to overcome nutritional problems and be able to improve immunity.